Homology modelling and comparative and docking analysis of two naturally occurring pancreatic glucokinase mutants - Janairo, Jose Isagani B. (Animo Repository, 2012)
The homology models of two naturally occurring pancreatic glucokinase mutants with contrasting enzymatic behaviours were successfully generated and accurately predicted. The homology models of the activated V367M and deactivated R369P mutants were used for comparative docking analysis in order to probe why such mutations led to either an increase or diminishment of enzyme activity. Results of structural characterization and docking simulations suggest that the small conformational changes are responsible for the observed variation in enzymatic activity. Iterative fitting and comparison of their respective Ramachandran plots reveal that these conformational changes are not sufficient to perturb the overall protein architecture. However, active site modelling showed that these conformational changes altered the manner of ligand binding, from which the observed contrasting enzymatic behaviours originate.